Modelling the yield curve: A two components approach - John Hatgioannides; Menelaos Karanasos; Marika Karanassou (Queen Mary University of London, Department of Economics, 2004)
Using parametric return autocorrelation tests and non parametric variance ratio statistics show that the UK and US short-term interest rates are unit root processes with significant mean reverting components. Congruent with this empirical evidence, we develop a new continuous time term structure model which assumes that the dynamics of the instantaneous interest rate are given by the joint effect of a (stationary) mean reverting component and a (nonstationary) martingale component. We provide a closed-form solution for the equilibrium yield curve when the temporary component is modelled as an Ornstein-Uhlenbeck process and the permanent component is modelled as an Arithmetic Brownian motion process.
Keywords: C20; E43; G12; 330; Term structure; Mean reversion; Random walk; Brownian motion; Variance ratio; Linear regression; Zinsstruktur; Stochastischer Prozess; Regression; Sch\~AƒÂtzung; Gro\~AƒÅbritannien; USA; Mean Reversion; Random Walk